Molecular Basis of Signaling Specificity of Insulin and IGF Receptors: Neglected Corners and Recent Advances - Siddle, Kenneth (Frontiers in Endocrinology, 2012)
Insulin and IGF receptors utilise common PI3K/Akt and Ras/ERK signalling pathways to mediate a broad spectrum of ‘metabolic’ and ‘mitogenic’ responses. Specificity of insulin and IGF action in vivo must in part reflect expression of receptors and responsive pathways in different tissues but it is widely assumed that it is also determined by the ligand binding and signalling mechanisms of the receptors. This review focuses on receptor-proximal events in insulin/IGF signalling and examines their contribution to specificity of downstream responses. Insulin and IGF receptors may differ subtly in the efficiency with which they recruit their major substrates (IRS-1 and -2 and Shc) and this could influence effectiveness of signalling to ‘metabolic’ and ‘mitogenic’ responses. Other substrates (Gabs, DOKs, SH2Bs, Crk), scaffolds (RACK1, β-arrestins, cytohesins) and pathways (non-receptor tyrosine kinases, phosphoinositide kinases, reactive oxygen species) have been less widely studied. Some of these components appear to be specifically involved in ‘metabolic’ or ‘mitogenic’ signalling but it has not been shown that this reflects receptor-preferential interaction. Very few receptor-specific interactions have been characterised, and their roles in signalling are unclear. Signalling specificity might also be imparted by differences in intracellular trafficking or feedback regulation of receptors, but few studies have directly addressed this possibility. Although published data are not wholly conclusive, no evidence has yet emerged for signalling mechanisms that are specifically engaged by insulin receptors but not IGF receptors or vice versa, and there is only limited evidence for differential activation of signalling mechanisms that are common to both receptors. Cellular context, rather than intrinsic receptor activity, therefore appears to be the major determinant of whether responses to insulin and IGFs are perceived as ‘metabolic’ or ‘mitogenic’.